TREATMENT OF CONCEPT “AESTHETIC CULTURE” IN THE PSYCHICAL-PEDAGOGICAL LITERATURE (Pedagogy of Higher and Secondary Education, 2022)
The article “Treatment of concept “aesthetic culture ” in the psychical-pedagogical literature ” is devoted to the analysis of various treatments of concept “aesthetic culture ” that has allowed the author to make the generalization necessary for it for carrying out of the further research work.